Profiling Safety Behaviors: Exploration of the Sociocognitive Variables that Best Discriminate Between Different Behavioral Patterns - Fugas, C. S. (2014)
This study combines contributions from both safety climate literature and prominent social influence theories. It was developed to identify the combination of sociocognitive variables that differentiate between different profiles of safety behaviors. This empirical approach has hardly been explored in the literature on behavioral aspects related to safety. The research setting for this study was a transportation company (N = 356). The results of discriminant analysis showed that different combinations of dispositional and situational influences may lead to diverse profiles of compliance and proactive safety behaviors. Perceived behavioral control was revealed to be the variable that best differentiated the group with more safe behaviors from the others. However, results also revealed that high attitudes and perceived behavioral control are very important, but not sufficient, to promote proactive safety. Co-workers’ descriptive safety norms were a major differentiating variable in proactive safety. Theoretical and practical implications of the findings are discussed.